On the issue of timely diagnostics of gender formation disorders - I. L. Nikitina; E. K. Kudryashova; A. M. Todieva; R. T. Badrutdinov; A. A. Kostareva (Лечащий Врач)
Importance of early diagnostics of gender differentiation disorders in children is discussed, different manifestations of this pathology are described so that they could be included in the spectrum of diagnostic search. We presented a clinical observation of two patients with gender formation disorders with karyotype 46ХУ, with identified mutations in the same gene of steroidogenic factor NR5A1, whom, on their birth, official female gender was given.